2000
DOI: 10.1007/s004400050257
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stochastic wave and heat equations

Abstract: We study nonlinear wave and heat equations on ‫ޒ‬ d driven by a spatially homogeneous Wiener process. For the wave equation we consider the cases of d = 1, 2, 3. The heat equation is considered on an arbitrary ‫ޒ‬ d -space. We give necessary and sufficient conditions for the existence of a function-valued solution in terms of the covariance kernel of the noise. IntroductionThe paper is concerned with the following stochastic wave equationand heat equationIn (0.1) and (0.2), u 0 and v 0 are given functions, f, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 14 publications
4
107
1
Order By: Relevance
“…As far as we know, there are no publications on the dynamics of coupled parabolichyperbolic stochastic partial differential equations, although stochastic parabolic and wave equations have been widely studied by many authors (see, e.g, the monographs Cerrai (2001), Da Prato andZabczyk (1996) and the references therein for the parabolic case and the papers Barbu and Da Prato (2002), Carmona and Nualart (1993), Dalang and Frangos (1998), Da Prato and Zabczyk (1992, Millet and Morien (2001), Millet and Sanz-Solé (2000), Peszat and Zabczyk (2000), Quer-Sardanyons and Sanz-Solé (2004) for the wave case).…”
Section: (L) and D(a)mentioning
confidence: 99%
“…As far as we know, there are no publications on the dynamics of coupled parabolichyperbolic stochastic partial differential equations, although stochastic parabolic and wave equations have been widely studied by many authors (see, e.g, the monographs Cerrai (2001), Da Prato andZabczyk (1996) and the references therein for the parabolic case and the papers Barbu and Da Prato (2002), Carmona and Nualart (1993), Dalang and Frangos (1998), Da Prato and Zabczyk (1992, Millet and Morien (2001), Millet and Sanz-Solé (2000), Peszat and Zabczyk (2000), Quer-Sardanyons and Sanz-Solé (2004) for the wave case).…”
Section: (L) and D(a)mentioning
confidence: 99%
“…Moreover, under various conditions on σ, (1.2) is necessary for the existence of a solution [10,26].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, pathwise uniqueness -and thus convergence of the approximations-holds if the coefficients satisfy Lipschitz conditions (see Peszat and Zabczyk [32]). But it can also be shown that pathwise uniqueness holds for the lattice systems if the drift coefficients are Lipschitz continuous and σ satisfies the conditions of Yamada and Watanabe [45].…”
Section: Formulation Of the Main Resultsmentioning
confidence: 99%
“…The case of a linear noise coefficient has been treated by Dawson and Salehi [10] and Noble [28]. Amongst others, Kotelenez [23], Peszat and Zabczyk [31,32], Brzeźniak and Peszat [2], Dalang [5], Manthey and Mittmann [25], Tindel and Viens [41] and Sanz-Solé and Sarrà [37] investigate solutions with Lipschitz coefficients. For some results on equations with non-Lipschitz coefficient see Viot [42], DaPrato and Zabczyk [34], Krylov [24] and Kallianpur and Sundar [20].…”
Section: Introductionmentioning
confidence: 99%